MEKANISME E-COMMERCE MELALUI BLOG DAN IMPLIKASINYA TERHADAP PENDAPATAN (STUDI KASUS PADA KOMUNITAS BLOGGER MALANG) - Firmansyah, Danny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The rapid development of technology today, allowing people to think creatively, to use technology to facilitate their lives, including their economic lives. One example is the development of technology used by many people today is the internet. The Internet allows people to get a lot of useful information for life, one media provider of information on the internet is a blog. In addition to being a means of exchanging information, the blog was also a means to earn an income for the owner of the blog, by putting ads on the blog. This study aims to provide an overview of how a blogger to manage their blog and how to earn money with a blog, ranging from choosing the theme of the blog to how bloggers receive revenue from ads they show on the blog, as well as the various constraints faced by bloggers. This study took a case study in Malang blogger community.Keyword : Blog, Blogger, Internet, Income.